Development of Resistance to Novobiocin, Tetracycline, and a Novobiocin-Tetracycline Combination in Staphylococcus aureus Populations - Vavra, James J. (1967)
The antibiotic sensitivity of the individual organisms of a bacterial population was determined to study the comparative rates of development of resistance of Staphylococcus aureus to novobiocin, tetracycline, and to a combination of these antibiotics. Serial subculture of S. aureus with the combination of novobiocin-tetracycline (N-T 2.5:1; the ratio in serum of patients dosed with Panalba) showed a significant retardation of resistance outgrowth compared with subculture in the presence of the antibiotics individually. Increase in organisms resistant to novobiocin seen after one N-T subculture was related to the “concentration gap” between novobiocin and tetracycline. Two additional subcultures with N-T caused little or no increase in organisms resistant to novobiocin, tetracycline, or to the combination. The data suggest that the retardation of further development of resistance was the result of tetracycline inhibition of novobiocin-resistant strains and vice versa.